The Role of Adversity Quotient and Authoritative Parenting on Academic Achievement of College Students in Denpasar City - I Gusti Ayu Rantika Astari Putri; Ni Luh Indah Desira Swandi (Journal of Psychology and Instruction, 2021)
This study aims to determine the role of adversity quotient and authoritative parenting on college students academic achievement. Subjects in this quantitative study were specifically college students in Denpasar, the biggest city in Bali which amounted to 106 people who were selected through a multi-stage cluster sampling technique. Instruments used were Adversity Quotient Scale, Authoritative Parenting Scale and students GPA. The results of multiple linear regression test showed a significance value of 0.000 (p <0.05) and an R value of 0.832 with a coefficient of determination (R Square) of 0.692, which means that Adversity Quotient and authoritative parenting style together play a role of 69, 2% towards academic achievement. The higher the level of Adversity Quotient and authoritative parenting, the higher the academic achievement of college students